2020
DOI: 10.1111/jch.13842
|View full text |Cite
|
Sign up to set email alerts
|

Secular trends in hypertension and elevated blood pressure among Korean children and adolescents in the Korea National Health and Nutrition Examination Survey 2007‐2015

Abstract: The prevalence of elevated blood pressure (BP) among US children and adolescents has reportedly declined over the past decade. As no Korean data have been analyzed, we aimed to determine recent trends in BP levels among Korean children and adolescents. This study examines data from the Korea National Health and Nutrition Examination Survey segregated into 3 time periods (2007‐2009, 2010‐2012, and 2013‐2015). A total of 7804 Korean children and adolescents aged 10‐18 years were included in the analysis. Hyperte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 27 publications
3
24
1
Order By: Relevance
“…This study results in 2017 and 2018 were consistent with previous study in Yunnan [29]. But it differed from most of the study findings [30][31][32]. However, the prevalence of hypertension in boys was higher than that of girls for the first time in 2019 in Yunnan, which was consistent with the national study [30].…”
Section: Discussionsupporting
confidence: 85%
“…This study results in 2017 and 2018 were consistent with previous study in Yunnan [29]. But it differed from most of the study findings [30][31][32]. However, the prevalence of hypertension in boys was higher than that of girls for the first time in 2019 in Yunnan, which was consistent with the national study [30].…”
Section: Discussionsupporting
confidence: 85%
“…23 According to the KNHANES, total caloric intake and fat intake increased between 2007 and 2015 in children and adolescents. 24 Approximately 10% of middle and high school students performed vigorous physical activity for more than 30 minutes 5 days per week, and almost half of high school students slept less than 6 hours per day. According to the KNHANES, the daily time spent in moderate-to-vigorous physical activity has not changed between 2007 and 2015 among those aged 10-18 years.…”
Section: Characteristics Of Obesity In Korean Children and Adolescentsmentioning
confidence: 99%
“…According to the KNHANES, the daily time spent in moderate-to-vigorous physical activity has not changed between 2007 and 2015 among those aged 10-18 years. 24 Low socioeconomic status was associated with obesity in children and adolescents using the KNHANES data. 25 These are well-known risk factors for developing overweight and obesity in children and adolescents.…”
Section: Characteristics Of Obesity In Korean Children and Adolescentsmentioning
confidence: 99%
See 1 more Smart Citation
“…And the difference in prevalence was caused by the age difference between subjects and the method of analysis.The prevalence of elevated blood pressure and hypertension in children is reported around 6% and 3%, respectively(9,29). In obese adolescents, the combinded prevalence increases to around 30%(29).Cho H et al reported the prevalence of hypertension increased over time, it was from 6.9% (KNHANES 2007-2009) to 9.0%, (KNHANES 2013-2015) in Korean children and adolescent aged 10-18 year(30). The prevalence of HTN were higher in boys than girls, and increased with severity of obesity.…”
mentioning
confidence: 99%